The larvae of two species of Bokermannohyla (Anura, Hylidae, Cophomantini) endemic to the highlands of central Brazil - Lins, Anna Carolina Ramalho; De magalhÃes, Rafael fÉlix; Costa, Renan Nunes; BrandÃo, Reuber Albuquerque; Py-Daniel, TainÃ Rapp; De Oliveira Miranda, NÚbia Esther; Maciel, Natan Medeiros; Nomura, Fausto; Pezzuti, Tiago Leite (Zootaxa, 2018)
Bokermannohyla (tribe Cophomantini) is an endemic genus of Brazilian treefrogs containing 32 species arranged into four phenetic groups. The B. pseudopseudis group includes nine species, which are typically found in rupestrian ecosystems of disjunct Brazilian mountain ranges. Tadpoles have been shown to be important sources of information for the taxonomy of this genus, although careful analyses of character variation and descriptions of internal anatomy remain scarce. Since the first description of B. pseudopseudis tadpoles was based on a mixed series containing specimens of B. pseudopseudis and B. sapiranga, we describe the larvae of these two species from their type localities, including their external morphology, oral cavity, and skeletal system. Tadpoles of B. pseudopseudis are easily distinguished from those of B. sapiranga by aspects of their coloration and characters of their oral disc (more labial tooth rows, more numerous submarginal papillae and flaps with labial teeth). These morphological differences may be diagnostic for these two similar species, whereas their chondrocranium, hyobranchial apparatus, and oral cavity are alike, suggesting less variability in these character systems between closely related species. Finally, we provide the first comparison of data on the skeletal system of Bokermannohyla and other Cophomantini, highlighting characters of potential relevance to the systematics of the tribe.